The demands of using e-learning in academic institutions from the point of view of the teaching (Journal of the College of Basic Education, 2022)
The world is witnessing a huge and accelerating technological revolution, as hardly a day passes without hearing about a new electronic product, or an update of an existing product, and this acceleration and technical progress was launched with the invention of the computer, and this progress is a feature of this age and a means for the progress and distinction of countries, as measured by the It advanced its scientific and technical production, and this revolution extended to include various areas of life, the most important of which is education, as this technology continued to support the teaching and learning processes, the delivery and storage of knowledge, and communication between different societies using tools such as (internet, radio, computers, teleconferencing, local channels or Satellite TV; CD-ROM; telephone; e-mail and others) to provide an interactive teaching-learning space that contains multiple sources without being restricted to place or time and relying on self-education and interaction between the learner and the teacher.The uses of computers and their applications in education, and the use of the Internet, electronic curricula and electronic classes, have expanded, which coincided with the current conditions and the Corona epidemic, which imposed on higher education institutions to work to meet the requirements of e-learning and develop the capabilities of faculty members to benefit from contemporary technical progress and transfer education a qualitative transfer by making Universities are the first beneficiary of this modern technological technology.